CODESRIA Bulletin Online, No. 12, September 2024 - Revisiting the Struggles for Academic/Intellectual Freedom and the Social Responsibility of Intellectuals in Africa: The Case of the Dar es Salaam and Kampala Declarations - J. Oloka-Onyango, (CODESRIA Bulletin, 2024)
Revised text of Keynote Reflections at the Colloquia on Academic Freedom and Social Responsibility, University of Dar es Salaam, Tanzania, 7th to 9th November 2023 and Eduardo Mondlane University, Mozambique, 15th to 17th April 2024 Academic freedom is about the building of a new civilization. It is the site of struggle for a truly pluralist democracy; a bastion against authoritarianism and a challenge to fundamentalism. Thandika Mkandawire Introduction The Dar es Salaam Declaration on Academic Freedom and Social Responsibility of Academics (hereafter the ‘DD’), and the Kampala Declaration on Intellectual Freedom and Social Responsibility (hereafter the ‘KD’) have their geographical origins in Tanzania and Uganda, respectively. The former was adopted in April 1990, and the latter came into existence in November of that year. Both were primarily authored by the same individual, Issa Shivji, law professor at the University of Dar es Salaam (UDSM). While the author might have been the same, the institutional parents of the declarations were different: on the one hand, the University of Dar es Salaam Academic Staff Assembly (UDASA), and on the other, the Council for the Development of Economic and Social Research in Africa (CODESRIA). The DD had six signatories, all of them being staff associations of the different institutions that came together to adopt the instrument. These were the Ardhi Institute, the Co-operative College, the Institute of Development Management, the Institute of Finance Management, Sokoine University and UDSM, a mix of traditional universities and other tertiary institutions, all of them public or created by the state. Those who attended the Kampala Symposium and adopted the KD were academics, students, administrators, trade unionists, donors and members of civil society, drawn from all over the African continent and the diaspora, and including several non-Africans. The DD has six parts: Basic Principales (which include Education for Human Emancipation; Obligations of the State and the Rights and Obligations of Communities); Academic Freedom (covering Rights and Freedoms; Autonomous Academic Organisations; Security of Tenure, and Obligations of the State and Administration); Autonomy of Institutions of Higher Education; Social Responsibility (addressing Responsibility of Institutions and Responsibility of Academics); Ratification and Association ; andDefinitions. The KD is made up of four sections: Fundamental Rights and Freedoms (comprising Intellectual Rights and Freedoms; right to autonomous organisations and autonomy of institutions); Obligations of the State; Social Responsibility; and Implementation. In order to provide some points for critical reflection and discussion on the two instruments, I have divided this text into three parts. First, I look at the broader history, the ethos and the legal implications of the two instruments. Then I consider the relevance of the two declarations to more contemporary issues in the area of academic freedom in Africa. Finally, I offer some concluding remarks on how we should proceed from here. The Context, Ethos and Legal Import of the Two Declarations The year 1990 fell in the early part of the post-Cold War era. In 1989 the Soviet bloc had disintegrated; around the world democratic change seemed afoot. Single-party dictatorships on the African continent were also being challenged and uprooted. Before 1990, ‘… only 5 African countries with universal suffrage had multiparty systems. By 1995, constitutional one-party or non-party systems were exceptions’ (Laakso 2022). At the same time, the scourge of International Monetary Fund (IMF) and World Bank structural adjustment programmes— including privatisation, the descaling of public services and the adoption of highly monetarist policies—was very much in vogue. It was the era of Margaret Thatcher in the UK and Ronald Reagan in the US. With respect to universities, the application of these policies involved, inter alia, cost-sharing, staff retrenchment, the abolition of student allowances and downsizing (Jjuuko 2021: 336–344). It was a time in which the crisis in African higher education reached its apogee (Mama 2006: 2). In sum, 1990 was a year of considerable hope but also of great change and formidable challenge. In Tanzania, Nyerere had stepped down five years earlier as founding president and Ali Hassan Mwinyi was in the middle of his ten-year rule in office. Agitation had commenced for the removal of the single-party monopoly exercised by Chama cha Mapunduzi (CCM)—the party of ‘liberation’—and indeed two years later Tanzania formally adopted a multiparty system of government. Things in academia were difficult, with UDASA becoming more vocal in speaking out against the austerity measures imposed to ‘restructure’ the economy. In Uganda, people were still reeling from six years of civil war (1981–1986) and nearly two decades of political strife. Museveni had been in power for only four years and was still in the honeymoon of his successful guerilla war: Ugandans (and many other Africans) loved him; he seemed to embody both Che Guevara and Patrice Lumumba. In spite of that popularity, one could discern even then the traces of the autocratic governance that would follow over the next four decades. Indeed, at best, that time could be described as one of ‘benevolent’ dictatorship. Unrest at Makerere—the only public university in the country then—was rife, leading to the first strike in the history of the institution by academic staff protesting the lack of a living wage (Nassali 2021). Nevertheless, Kampala was chosen as the site for the first-ever continental conference on academic freedom because the light in Uganda seemed to be brighter than in many other countries of the region (Mamdani and Diouf 1994). Given this history, the two documents bear a number of similarities (beyond the same authorship), but there are also differences. Both instruments are broadly concerned with: Articulating the exact nature and character of the right to academic freedom as a subcategory of the broader human and democratic rights that belong to all human beings; Highlighting the specific struggles that confront African academics in attempting to ensure the actualisation of those rights; Outlining the obligations of the state and tertiary institutions in facilitating, and protecting against the violation of, those rights; and Pinpointing the nexus of the right of academics to freely teach, research and comment on all manner of issues, and the broader communities—organised and otherwise—that face similar challenges to their rights of organisation, expression and association. Structurally, the DD comprises fifty-three articles, whereas the KD has only twenty-six. Perhaps the difference is explicable in terms of the time available for their formulation and the distinctive goals to which they were devoted—the DD to a local, geospecific institutional reality, and the KD to a much larger region. Even so, the Dar Declaration was very much Pan African in inspiration and global in conception. Although the measures of privatisation were already underway in many countries around the continent, it is true to say that most of the representatives who participated in the formulation of the two declarations came from state (or) public universities and tertiary institutions. Also, much more focus was placed on faculty than on students. Both instruments sought not simply to highlight and protect the everyday struggles of intellectuals and academics but to link them with the lived conditions of those in the wider community. Thus, as key intellectual and activist instruments in the struggle for academic freedom on the continent they also fed into the broader struggles for democratisation and development that were in play around Africa at the time. I describe them as ‘intellectual’ instruments because they were concerned not only with the ivory tower but sought to link the struggles at the academy with the broader struggles on the streets, in the communities and in the villages. In that sense the instruments were hortatory, or mobilising: while declaring that it was necessary to ensure that the agency of academics and intellectuals was protected, they also made scholars critical actors in the wider process of development and struggle. The DD and the KD could be described as ‘activist’ because they belong within the canon of radical rather than official (or statist) instruments of legality. In contrast to the Lima Declaration on Academic Freedom and Autonomy of Institutions of Higher Education—a tract adopted in 1988 under the auspices of the World University Service (WUS) (Fernando 1989; Ihonvbere 1993: 45–46)—the DD was clearly influenced by the Universal Declaration on the Rights of Peoples (aka the Algiers Declaration), which was the populist counterpart to the African Union’s Banjul Charter. The Dar Declaration declared: These are times of crises. But they are also times of hope. As People’s free and independent existence is in question, they are beginning to question the existence of unfree and right-less polities. We, as academics, intellectuals and purveyors of knowledge, have a human obligation and a social responsibility towards our People’s Struggle for Rights, Freedom, Social Transformation and Human Emancipation. Our participation in the struggle of our people is inseparably linked with the struggle for the autonomy of institutions of higher education and the freedom to pursue knowledge without let, hindrance and interference from persons in authority. (Para. 4, Preamble to the DD) For its part, the Kampala Declaration stated, African people are responding to these intolerable conditions by intensifying their struggles for democracy and human rights. The struggle for intellectual freedom is an integral part of the struggle of our people for human rights. Just as the struggle of the African people for democracy is being generalised, so too is the struggle of African intellectuals for intellectual freedom intensifying. (Para. 2, Preamble to the KD) Indeed, the Kampala Declaration was drafted in the wake of a massacre of students at Lubumbashi University in Zaire (present-day DRC) as former dictator Mobutu Sese Seko grappled with growing unrest against his autocratic rule. And only a month after the symposium ended, two Makerere students were gunned down by state operatives, eventually leading to the closure of the university for an extended period of time. Ultimately, although written in conditions of considerable strife and challenge, the two declarations sought to invoke hope. They exemplified (albeit unconsciously) the Struggle Theory of Human Rights (Heyns 2001), an issue that I will come back to. The Kampala instrument proclaims: ‘members of the African intellectual community have an obligation both to fight for our rights as well as contribute to the rights struggle of our people’, while the Dar Declaration states, ‘But rights are not simply given; they are won. And even when won, they cannot endure unless protected, nurtured and continuously defended against encroachment and curtailment’. It is thus not surprising that, spurred by the Kampala Declaration, the 1995 Constitution of Uganda declared, among other things, ‘Every person shall have the right to—(b) freedom of thought, conscience and belief which shall include academic freedom in institutions of learning’ (Article 29(1)(b), 1995 Constitution of the Republic of Uganda). Continent-wide, fourteen (25.45 per cent) out of fifty-five countries make specific reference or give explicit recognition to ‘academic freedom’ in their constitutions (Appiagyei-Atua, Beiter and Karran 2016). In the wake of the two declarations, the reach of protections of academic freedom extended to the continental level, with the African Commission on Human and Peoples’ Rights giving explicit recognition to the need for states to refrain from suppressing academic expression, in the decision in Kenneth Good v. Botswana: In the opinion of the Commission the article that was published by the victim is a purely academic work which criticizes the political system, particularly presidential succession in Botswana. There is nothing in the article that has the potential to cause instability, unrest or any kind of violence in the country. It is not defamatory, disparaging or inflammatory. The opinions and views expressed in the article are just critical comments that are expected from an academician of the field, but even if the government for one reason or another considers the comments to be offensive they are the type that can and should be tolerated. In an open and democratic society like Botswana, dissenting views must be allowed to flourish even if they emanate from non-nationals.1 Perhaps a major failing of both declarations was in not providing mechanisms for the implementation of the critical elements of academic freedom that they propounded. The DD reduced follow-up to ‘Ratification and Accession’, elaborating a threshold figure of additional institutions for the conferment of legality/legitimacy on the instrument, and providing for additional higher education staff associations to join the original signatories. The next step after adoption of the declaration was for ‘staff associations to pressurise the respective administrations at their institutions to accord the declaration formal recognition. Eventually, the government itself was to be approached to accord the Declaration political acceptance’ (Shivji 1991: 128), although it is not clear whether this was ever done. For its part, the KD called on the intellectual community to ‘… further elaborate and concretise the norms and standards’ set out in the instrument, and to ‘… form its own organisations to monitor and publicise violations of the rights and freedoms stipulated therein’. All in all (and despite the limitations of both time and place), the promulgation of the two instruments represented a significant milestone in the elaboration of standards and principles for the enhanced observation of the right to academic freedom on the continent. This was in respect of the right as a subset of broader rights and freedoms (such as those to expression, organisation, opposition and association) and in fleshing out the broader contours of the right. Secondly, the instruments provided an African perspective on an issue that hitherto had been viewed mostly through Western lenses of analysis. In sum, the two declarations brought to the fore of intellectual debate on the continent a right that had been largely neglected. More importantly, the two instruments went beyond intellectual navel-gazing, by cogently and convincingly linking the struggles of a fairly elite and relatively more cushioned section of African society to those of the wider community. Nevertheless, having been passed in the era BG (Before Google) or BI (Before the Internet), how can these instruments address the many challenges and concerns of academic life in the twenty- first century? This is the main focus of the remainder of my article. Critical Developments in Academic Freedom since the 1990s Although the two declarations were explicit in addressing the ills of the day, many of the problems with which they were concerned continue into the twenty-first century, and indeed, new issues can be added to the list. I would like to focus on those issues that I believe are most prominent in the contemporary context, by way of updating the focus of the declarations and in reflecting on the way forward. State control and dominance Despite the decrease in outrightly fascist regimes of governance and the progress away from total dominance by the state over African universities in the twentieth century, the state—and especially undemocratic governance—was still prominent in the life of many universities and therefore in influencing the condition of academic freedom on most campuses in Africa in 2023. One could say without contradiction that the vast majority of African governments pay only lip- service to the basic elements of the right to academic freedom outlined in the two declarations. Most adopt a narrow perspective that recognises the right to teach and research but disregards and undermines academic freedom as a democratic and basic human right integral to the wider struggles for individual actualisation and community activation. Put differently, once the deliberations at campus move beyond the university gates and enter the street, the ‘ghetto’ or the village—the radio, the Internet or the vlogosphere—the response of the state ceases to be benign. And what might be considered benign by an ordinary observer may be regarded as subversive, seditious or even treasonous by the state. Hence, state interventions—both subtle and direct— that offend academic freedoms abound in 2023. Some of the indirect methods deployed by governments in contemporary Africa include using fiscal, financial and legal incentives and penalties to influence research and teaching. Such measures are accompanied by bullying and threatening ‘recalcitrant’ staff, even to the extent of instituting civil and criminal charges against them. States have also been involved in sabotaging, manipulating or gerrymandering electoral processes for staff, student and alumni organisations where such a franchise actually exists. Female academics face so-called ‘marriage and baby’ penalties, being compelled to make a choice between family and career (Appiagyei-Atua et al. 2016). Although elections have replaced ministerial or presidential appointments in many instances, in several countries the selection of senior academic and administrative staff still vests in government authorities, with numerous implications for the state of democratic action and mobilisation on campus. Such powers are used to secure the deployment of university management and governing councils in order to guarantee pliant or complicit state agents who will ensure that the will of the government is done. At Makerere, the chair of the University Council is closely associated to the Minister of Education who also doubles as the First Lady; her son-in-law is the chair of the Appointments Board. It is worth mentioning that the First Lady’s husband—who also happens to be the president—is the Visitor to the university! More overtly coercive measures have also been recorded. Between 1 September 2021 and 31 August 2022, scholars faced state-invoked attacks in various countries—Cameroon, Democratic Republic of Congo (DRC), Egypt, Ethiopia, Guinea, Lesotho, Nigeria and Sudan (Kigotho 2023). Intellectuals were subjected to arbitrary arrest and imprisonment, restrictions on free movement and a panoply of legal and extralegal measures that affected their academic freedom directly and otherwise. At the same time, there were (and still are) intrusions by non-state actors, including armed militants and extremist and off-campus vigilante groups. In the wake of the Tigrayan uprising in Ethiopia, university scholars and institutions were targeted both by Ethiopian government forces and fighters of the TPLF. Similarly, Garissa University College in Kenya and the Ahmed Baba library in Timbuktu were raided by armed groups. Although Boko Haram has largely targeted primary and secondary schools in Northern Nigeria, universities have not been spared (Okocha 2020). Even as the universities in this region soldier on, they are affected by high dropout rates and the reluctance of non-natives to study there. Today, the admonitions against the state and the calls to protective action made by the two declarations still hold sway. But what about the situation within universities? Universities as sites of repression and micro-aggression While the authors of the two declarations of 1990 largely had the state and external actors in mind, they were also concerned about excessive control and domination within the institutions in which they operated. Today, many universities—private and public—are tormented by what I can only describe as the Human Resources Demon (HRD). That demon’s reach extends from making spurious rationalisations to downsize academic staff to imposing ludicrous conditions for retrenchment coupled with introducing new methods of monitoring staff attendance and performance in class. At Makerere, the latest of a string of managerial measures designed to both cull and cow the staff is the biometric monitoring of staff attendance on an eight-to-five (8 a.m.—5 p.m.) schedule, capitulating to the demand by the state that academics be treated no differently from workers employed in direct government service, with all the implications this entails. Security of tenure is no longer guaranteed as universities move from fixed tenure to periodic contract (and even piece-rate and adjunct) relationships. The processes of initiating, renewing and terminating these agreements are rife with all manner of machinations, coercions and unconscionable conditions. These methods of internal institutional collaring at African universities amount to new forms of dominance and repression exercised from within. In this respect, the state has a pliant and co- operative agent doing its bidding, albeit in the name of efficiency, the improved management of resources and the pursuit of compliance with ‘international’ standards of performance appraisal that do not reflect the local context or reality. Needless to say, the ultimate result is academic self-censorship, when scholars are unsure of whether what they say or uncover in the course of challenging the status quo—nationally, locally or even within their departments and faculties— may return to haunt them in the politics of academic growth and promotion. While recognising that the two declarations primarily focused on the external and structural factors that inhibit the recognition and protection of the right to academic freedom, they were also concerned with the social responsibility of academics, albeit to a lesser degree. It remains an issue of concern today. One can do no better than to quote Zeleza: Besotted by opportunism, careerism, parochialism, factionalism and academic intolerance, academics have often weakened their collective defense against state assaults, and by defining academic freedom in narrow and elitist terms, as a professional right unencumbered by social responsibility, they often forfeit popular support. Thus, the road to academic freedom must begin with honest self-criticism among academics themselves, of their practices and values. (Zeleza 2003: 170) Today, the call for the heightened responsibility of African academics is still heard, especially regarding issues such as sexual harassment, the maintenance of ethical standards, moonlighting and the neglect of teaching, mentoring and supervisory obligations. African academics need to reinvigorate their commitments to what they pledge to their students and to the wider community. It is no longer tenable to point out the actions of the state and international financial institutions that inhibit academic freedom while ignoring our own (Adesina 2020). These are responsibilities that should not be forgotten and need re-emphasising. Privatisation and the proliferation of universities In 1990, most universities in Africa were public institutions, and therefore the tenor and focus of the two declarations was largely on institutions directly (and majorly) supported by the state. The spate of privatisation that spread across Africa was just beginning to manifest itself on the back of the SAPs that were pursued at the time. Although the rationale for privatisation made some economic sense given the myriad problems confronted by state enterprise, the policy was a thinly disguised entry point for a much more insidious process—the phenomenon of commercialisation, or what I would describe as the balance-sheet approach to higher education. Today, rather than being seen as receptacles of learning, students are viewed as commodities for capture; the larger the number, the higher the returns, regardless of the quality of education disseminated. The drive towards making the university ‘entrepreneurial’ in the wake of reduced state funding has led to the uncritical acceptance of funding from business and external donors, neither of whom are necessarily altruistic nor genuinely developmental in their goals. Is it any surprise that the largest external donor resources in most African universities are directed towards areas such as public health, which is largely a discipline of containment? Accompanying the above developments is the emergence of micromanagers, administrators who are enamoured much more with superficial metrics of success, quantitative as opposed to qualitative outputs and especially the ogre of artificial university rankings than with protecting university autonomy, championing the rights of faculty and students or protecting those who stand to benefit least from these developments. The consequence of this situation is grade inflation, the assembly-line production of graduates, the innovation of all manner of for-payment short-courses, and an epidemic of schools offering a plethora of under- and postgraduate classes for which there is scant national capacity for absorption. Those impulses extend to attempting to influence curricula reform and even the tenure of research being pursued. There are also concerted efforts at divide-and-rule of African academic communities, with fissures being forced between the STEM (Science, Technology, Engineering and Mathematics) courses on the one hand and the SOSA (Social Sciences and Arts) disciplines on the other. Under the pressure of privatisation and in the name of revenue generation as state subsidies to tertiary education have fallen, not only have public universities assumed models of operation that are more akin to business and commerce but the motive of operation has also become much more narrowly entrepreneurial than utilitarian. As Mahmood Mamdani pointed out, many contemporary African intellectuals and academics have become ‘scholars in the marketplace’ (Mamdani 2006). University education has become a commodity traded on the market to the highest bidder. I will not talk about the massification of doctoral awards that have accompanied these processes—many of which can be purchased at whim and for a song from fly-by-night organisations masquerading as universities—but the implications for the academy in general, and the state of debate, critical research and intellectual engagement, is largely negative. To make matters worse, what can only be described as the ‘dollarisation’ of the academy has grown apace with a premium placed on disciplines that are ‘relevant’ and ‘productive’. Within this paradigm, the measurement of academic value is calibrated much more in terms of the ability to attract external resources (a quantitative computation) than of one’s contribution to the advancement of science, inquiry and debate, which are qualitatively beneficial inputs to the wider society. Ironically, even as university education becomes much more of a private commodity than a public good, intellectuals and scholars who operate in private universities face much more precarious conditions of tenure as well as self-censorship than their counterparts in the public sphere, if only because their tenure is much less secure. To speak of academic freedom when next month’s pay cheque is not guaranteed, let alone when faced by overt institutional strictures on religious and ideological beliefs, is really a myth. Sex, Gender and Sexuality Neither the DD or KD pay much attention to issues relating to gender or sexuality, save for making broad platitudes condemning prejudice, supporting affirmative action and taking note of the problem of harassment. In a critique of the KD, Amina Mama states, There is no specific mention of the right to freedom from gender, ethnic, class or religious discrimination, or to equal treatment within academic institutions. The declaration refers to an abstract ‘African intellectual’ which a generous interpretation could take to include women and members of other marginalised groups. The declaration is inconsistent with regard to the use of gender- inclusive language, and there is no acknowledgement of the gross under- representation of women and other marginalised groups in the academy, or of the extent of gender discrimination, sexual harassment and abuse that occur within the academic community. (Mama 2006: 11) The above are serious (and somewhat surprising) omissions, especially from the KD where the debate at the Kampala Symposium about gender-based discrimination, sexual harassment and the dearth of senior female academics and administrators was quite intense (Oloka-Onyango and Tamale 2000: 12–18). As pointed out by Ebrima Sall, Gender is one of those determinants of social relations within the academy, although gender relations are also over-determined by other factors. Discrimination exists between male and female teachers and students. Gender is also a factor in the relations between female students and male teachers, between university administration and female teachers and students and in the relations that the latter have with, and in how government officials perceive them, and civil society. (Sall 2000: x) Needless to say, the issue of gender relations in the African academy remains a serious one today, meriting a much more comprehensive and critical approach than was offered in either declaration (Mama 2011). Such an approach would necessarily have to comprehensively tackle issues such as access and equity, opportunity and inclusion, sexual and gender-based violence (SGBV), and representation, voice and the rates of attrition among female students and faculty (Tamale 2021: 261–263). Added to the above is the much more controversial issue of gender and sexuality, encompassing sexual orientation and gender identity/expression. Although ostensibly arenas of free thought and discussion, the levels of prejudice, intolerance and outright hostility over these important issues in many African universities is frightening. In this respect, illiberal elements on campus combine with those in the state and in religious institutions in the pursuit of actions that negate the essential elements of academic freedom for non-conforming individuals. For example, in Uganda’s Anti-Homosexuality Act (AHA) of 2023, there are express provisions which affect freedom of assembly and association and the rights to privacy and dignity. But they also affect the right to hold opinions as well as to receive and share information, both of which are the bread and butter of the academic profession. Not only did the law receive tremendous backing from Parliament but not a single university staff association or students’ guild spoke against its draconian provisions, preferring instead to maintain a stoic silence on the issue. In the immediate aftermath of the AHA, seminars were convened at Makerere and other university campuses around the country to mobilise students in the ‘fight’ against homosexuality. Under the law, similar meetings to urge action against homophobia would face numerous restrictions and even penal sanctions in the name of battling the so-called ‘promotion’ of the practice. And yet it needs to be underscored that freedom of expression—on issues kosher and taboo alike—is the core of academic freedom. Academics who fail to speak out about the plight of other repressed minorities should be aware that it is only a matter of time before the guns will be trained on them. Indeed, in a letter to all research ethics committees, institutional animal care and use committees and ‘distinguished researchers’, on 27 October 2023 the Uganda National Council for Science and Technology—the statutory body mandated with the research oversight function in the country—noted, inter alia: Whereas Government encourages research into any area that is crucial to human life and advancement, where a person involved in research detects that a crime under the AHA was committed against a child or vulnerable person, he or she is required to report and, it is an offence if the person does not report the perpetrator to police. The duty of confidentiality in research may be waived for purposes of reporting to the relevant authorities the commission of an offence, where a person involved in research detects that an offense under the AHA or any other laws was committed or intends to be committed. (UNCST 2023: 2) The gods of 1984 have truly come home to roost. In this respect, German theologist Martin Niemöller’s 1946 poem is a telling caution: First they came for the socialists, and I did not speak out because I was not a socialist. Then they came for the trade unionists, and I did not speak out because I was not a trade unionist. Then they came for the Jews, and I did not speak out because I was not a Jew. Then they came for me and there was no one left to speak for me. Although in many respects the debate over gender and sexuality is the consequence of unrequited cultural battles being fought out in Western academies, courts and religious institutions, it points to a much wider issue of global domination and the decolonial struggle. Confronting Global Domination in the Wake of Decolonial Studies and Struggles Although implicit in several provisions of the two instruments, the matter of external influence and domination is only vaguely given reference and articulation. Nevertheless, at the Kampala Symposium, donor influence and control received considerable attention, and remains a major subject of concern with respect to the full realisation of the whole range of academic freedoms to which the African academy aspires. Donor-dictated teaching and research priorities often garner priority over locally generated initiatives, with obvious implications for academic freedom on the continent. That is not to mention the failure to disrupt the enduring legacies of coloniality in higher education. Both declarations were crafted largely within the existing framework of Western modernity and Eurocentric approaches to higher education. However, aside from the usual foreign (mainly Western) suspects with dubious interests and self- motivated stakes in the African academy, there is a new external actor that has recently found expression in the annals of teaching, research and other scholarly endeavours on the continent. In 1990, China was but a blip in global political and intellectual discourse. Thirty-three years later, China is a phenomenal international power whose actions on the political and economic scene have the Western powers (which have traditionally dominated the global arena) on tenterhooks. Invariably, there are also several implications for academic freedom and the relationship between African academies, Chinese institutions of higher learning and, of course, the Chinese government. Taking the cue from their counterparts in the state, the warm embrace for China on many African university campuses, exemplified by the rise in academic co-operation between the two over the last twenty years, is notable. Exemplifying this embrace is the growing influence of Confucius Institutes (CIs) on the continent—there are currently sixty-one in forty-six African countries (Sawahel 2023). While many African scholars welcome the opportunities that CIs and other Chinese initiatives may facilitate, they have arguably ‘become a site by which external forces can influence curriculum and the allocation of resources to their own ends’ (Homawooa and Conyers 2021: 3). There is no doubt that these new relationships with China raise serious questions about academic freedom even as African academics support the collaboration as less intrusive and domineering than it has been with scholars and institutions from the West. In this Confucian embrace, are we substituting one imperial power with another, trading in Washington and London for Guangzhou and Beijing? The somewhat uncritical acceptance of the Chinese academy raises new questions about the decolonial project that the two declarations only implicitly embraced, albeit in nomenclature that is not in vogue today. Movements such as #RhodesMustFall in South Africa and other student- led actions targeting outdated and (neo)colonial curricula highlight starkly the manifestly alien and arid contexts in which African academies continue to be mired, decades after the achievement of formal independence. As Tamale points out, African universities are the ‘… example par excellence of the continued sustenance of the colonial project’ (Tamale 2020: 235). Certainly, if academic freedom is to become a full reality on African campuses, then the decolonial project needs to be engaged with much more wholeheartedly. Academic freedom in Africa must encompass the right to indigenous knowledge systems and practices in order to actualise epistemic decolonisation on the continent. Post-Pandemic Academic Blues Tanzania was among the handful of African countries that never fully closed down during the Covid-19 pandemic that stunned the world in 2020. Uganda not only locked down but also invoked some of the most stringent conditions of pandemic management (aka dictatorship) witnessed anywhere; indeed, many other countries around the continent imposed restrictions which impacted directly and otherwise on academic freedom. Whichever side of the spectrum our countries fell, today we are all living in a post-pandemic era and I believe that context has serious implications for the issues of academic freedom with which the two declarations were concerned. During the pandemic the academy in Africa (as elsewhere) was affected by sweeping university and library closures, the sudden shift to remote work, learning and teaching (‘online-isation’), virtual conferences (‘Zoomification’), and mobility restrictions for researchers and students (Benner and Brechenmacher 2021). Correspondingly, the new methodologies for addressing the pandemic brought with them increased opportunities for the surveillance of research, teaching and discourse, heightened possibility for sanctions, restrictions and self-censorship, and academic isolation (Kinzelbach, Saliba and Spannagel 2021). There was also a class dimension to the issue, as many African universities and students were affected by the obvious resource constraints involved in accessing and using data, computers and other smart devices, all of which were compounded by an unreliable supply of electricity. However, even after the pandemic was declared over and its associated restrictions were lifted, the academy continues to be affected by the public health and commandist approach to learning left in its wake. Online classes are obviously great tools for instantaneous non-physical learning. Nonetheless, they can also be avenues for censorship, harassment, surveillance and other forms of political interference by autocratic and authoritarian governments, with a telling (and even chilling) impact on faculty and student free speech. That is not to mention the looming danger of Big Data and algorithm hegemony, both of which have serious implications for academic freedom in the present century (Harari 2018). Given how much African academies are reliant on foreign technologies, the impacts on academic self-determination are considerable. Coupled with all this is the de-communitisation of the university. With classes, meetings and conferences migrating off campus and online, the idea of an academic community in its traditional sense—a space of vibrant, invigorating physical and intellectual contact—has been greatly affected. Community has been ‘virtualised’ and (as with the notion of ‘friends’ and ‘friendship’ on social media sites like Facebook) the very notion and meaning of an ‘intellectual community’ has been reconfigured. Movements geared towards community mobilisation and concerted and deliberated action for academics has been greatly affected by these developments. The Question of Implementation and Prospects for Concrete Action As already pointed out, the two declarations paid scant attention to the issue of implementation, and indeed scholars such as Kanywanyi and Ihonvbere made this point with varying degrees of clarity. Writing soon after their adoption, Ihonvbere complained that although the declarations were available in Western academies they were little known (much less circulated) in African universities (Ihonvbere 1993: 48). Unfortunately, the very same criticism could be levelled today, given that popular knowledge about both instruments is relegated to the occasional workshop or conference, but with no clear and consistent re-articulation of the basic tenets to which they were devoted. Clearly, there is a need to re-popularise the two declarations as instruments of relevance to the contemporary struggles over academic freedom that affect the African intelligentsia today. A related matter is the extent to which the two declarations have played the envisaged role of mobilising academic communities to rally around the protection of the rights that they adumbrated. Regarding follow-up, questions of monitoring and ensuring compliance, one critic argued that although the declarations made lofty proclamations, these were left ‘… hanging in mid-air without any legs to stand on, any heads to carry them forward or any hands to guide them along the charted path’ (Kanywanyi 2006: 71). The mere adoption of the declarations could not translate into implementation. However, there was a need to support them by organisation, mobilisation, education and ultimately, political activity (Ihonvbere 1993: 50). The problem with the absence of a process of continuous mobilisation or mechanisms of following up the critical elements in the declarations is that neither the universities nor the states that were the primary focus of concern have been under any pressure to ensure that the basic elements of the instruments are not subverted. Obviously, universities that are perceived not to be functional to the preservation and extension of the state are unlikely to be supported. Despite the declarations having been around for more than three decades, the fact is that academic freedom in Africa is still grossly understudied and largely unprotected on the continent (Adu and Odame 2023). Moreover, in terms of implementation both the DD and the KD have in some respects been overtaken by instruments that came much later, such as the November 1997 UNESCO ‘Recommendation Concerning the Status of Higher Education Teaching Personnel’. The Recommendation was endorsed by the International Labour Organization (ILO), thereby linking it to the trade union movement. The UNESCO Recommendation deals with indicators relating to academic freedom in four broad areas of concern: institutional autonomy; individual rights and freedoms; institutional self- governance; and tenure. Furthermore, Chapter X (on Utilisation and implementation) of the Recommendation consists of four paragraphs, which make the following stipulations: Member States and higher education institutions should take all feasible steps to extend and complement their own action in respect of the status of higher education teaching personnel by encouraging co-operation with and among all national and international governmental and nongovernmental organisations whose activities fall within the scope and objectives of this Recommendation. Member States and higher education institutions should take all feasible steps to apply the provisions spelled out above to give effect, within their respective territories, to the principles set forth in this Recommendation. The Director-General will prepare a comprehensive report on the world situation with regard to academic freedom and to respect for the human rights of higher education teaching personnel on the basis of the information supplied by Member States and of any other information supported by reliable evidence which he/she may have gathered by such methods as he/she may deem appropriate. In the case of a higher education institution in the territory of a state not under the direct or indirect authority of that state but under separate and independent authorities, the relevant authorities should transmit the text of this Recommendation to institutions, so that such institutions can put its provisions into practice. Via this mechanism, UNESCO is able to provide a device that draws member states into a periodic reporting process, which ensures that the issue of academic freedom is not swept under the carpet. This is done through the Committee of Experts on the Application of the Recommendations Concerning the Status of Teaching Personnel (CEART), which meets and reports every three years. Unfortunately, the instrument is not Afrocentric but assumes a ‘universal’ academic and functioning institutional context (Mama 2006). There are also obvious limitations accompanying an intergovernmental mechanism that is dominated by states. Nevertheless, it points the way to more concrete action. With respect to recording and monitoring academic freedom violations, a US-based organisation called Foundations for Individual Rights in Education (FIRE) performs the function of cataloguing violations of academic freedom against academicians around the world and admonishing governments responsible for the attacks. And the Global Academic Freedom Index provides a quantitative assessment of the state of the right in numerous countries around the world. Needless to say, both these bodies pursue a largely Eurocentric approach to academic freedom that only tangentially addresses the major concerns of African intellectuals and academics. Where then, does this leave initiatives from the continent like the DD and the KD? In a paper written eight years ago, Kwadwo Appiagyei-Afua argued that there is a need for an African Charter on Academic Freedom, or what he called a Magna Charta Libertatis Academicae (Appiagyei-Atua 2015b). He points out that the ‘previous impetus towards protecting academic freedom provided by the Kampala and Dar es Salaam Declarations has been dissipated. Moreover, the historical circumstances that gave birth to them has changed dramatically’ (ibid.). As a legal academic, my first instinct is to support such an initiative. However, this might be a long and arduous task. Ipso facto it will involve governments in an exercise they might not have any interest in pursuing. In addition, there are clear limitations to taking recourse in law as a tool for social and institutional change. This brings us back to the original impetus, and the institution that was responsible for the DD and the KD, namely CODESRIA. Article 26 of the KD states that ‘It is incumbent on the African intellectual community to form its own organisations to monitor and publicise violations of the rights and freedoms stipulated therein’. In the mid-1990s, CODESRIA established an Academic Freedom Unit to take on this function, but it seems to have petered out. CODESRIA’s vast panoply of committed scholars and researchers and its co-operative links with institutions and academic networks on the continent place it in the best position to set in motion a process which gives voice to the demands articulated in the DD and the KD, updated and reinvigorated by the more contemporary issues that affect the African academy, including the rights of female academics, the situation of students, organic (non-institutional) intellectuals and the struggle against new forms of coloniality. Whether this call can be taken up should be the main issue for discussion. Conclusion The authors of the Dar and Kampala declarations set out to demonstrate that academic freedom is not some esoteric and elite privilege exclusively for those in the ivory tower. Rather, they wanted to demonstrate that the manner in which we teach and learn is crucial to the manner in which we govern, create institutions and exchange data and information. Nevertheless, it is a truism that states are reluctant to champion and actively protect human rights, especially of individuals, groups or communities who may ultimately undermine their control of power. Regarding universities and the academic freedom that we cherish, there is no doubt that without the continuous and aggressive promotion and protection of this right, its full realisation and enforcement will remain a mirage. If there is one message we should take from my reflections, it is: Organise, don’t agonise. ALUTA CONTINUA! Notes 1 Kenneth Good v Botswana, Para. 199 (ACHPR Decision 315/05), https://caselaw.ihrda.org/en/entity/rfrrylm0oy?page=1